IMPLEMENTASI SEMANGAT NASIONALISME PEMUDA PANCA MARGA MELALUI KEGIATAN SOSIAL KEAGAMAAN DI KABUPATEN PRINGSEWU - Mohamad Nurdin (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
Nationalism is an important foundation in maintaining the integrity of the diverse Indonesian nation. The role of youth as strategic agents of change is a key factor in instilling and actualizing national values. Pemuda Panca Marga, as an organization and forum for the descendants of veterans, has a moral obligation to maintain nationalism and national spirit amidst the emerging crisis of identity politics. This study aims to analyze the implementation of youth nationalism through socio-religious activities in Pringsewu Regency. The study used a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation of the activities of youth organizations, particularly Pemuda Panca Marga (PPM), in their involvement in securing religious celebrations and interfaith social activities. The results show that the implementation of Pemuda Panca Marga's nationalism in Pringsewu is clearly manifested through active involvement in socio-religious activities and securing Christmas celebrations.